2007
DOI: 10.1209/0295-5075/77/57005
|View full text |Cite
|
Sign up to set email alerts
|

Intraband vs. interband scattering rate effects in neutron irradiated MgB 2

Abstract: One of the most important predictions of the two-gap theory of superconductivity concerns the role of interband scattering (IBS) by impurities. IBS is expected to decrease the critical temperature, T c , of MgB 2 to a saturation value of about 20 K, where the two gaps merge to a single one. These predictions have been partially contradicted by experiments. In fact, T c does not saturate in irradiated samples, but decreases linearly with residual resistivity and the merging of the gaps has been observed at a mu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 39 publications
1
37
0
Order By: Relevance
“…A review of the radiation damage of MgB 2 films and polycrystalline samples describes a significant effect of α-particle and neutron irradiation on T c and H c2 [34]. Neutron irradiation of MgB 2 has led to a complete suppression of T c [35,36], which prompts the question of the nature of defects produced by neutron irradiation with a possibility of a nuclear transmutation of boron. This and other issues, such as the influence of irradiation on intergrain coupling, are also discussed in Ref.…”
mentioning
confidence: 99%
“…A review of the radiation damage of MgB 2 films and polycrystalline samples describes a significant effect of α-particle and neutron irradiation on T c and H c2 [34]. Neutron irradiation of MgB 2 has led to a complete suppression of T c [35,36], which prompts the question of the nature of defects produced by neutron irradiation with a possibility of a nuclear transmutation of boron. This and other issues, such as the influence of irradiation on intergrain coupling, are also discussed in Ref.…”
mentioning
confidence: 99%
“…In fact the single electron interband (r to p-band) impurity scattering due to atomic substitutions remains suppressed, with the inversion of the r to p-gap hierarchy [18] providing a clear support for earlier theories and experiments [21][22][23][24][25]. Klie et al [26] and Putti et al [27] have carefully studied the effects of intraband single electron impurity scattering in the electronic and transport properties. Carrington et al [28] have reported de Haas-van Alphen (dHvA) studies of the electronic structure of Al-doped crystals of MgB 2 .…”
Section: Introductionmentioning
confidence: 71%
“…This result demonstrates that intraband scattering causes smearing of the DOS and further diminishes T c by a similar mechanism to that previously observed in superconductors with the A15 structure, such as Nb 3 Sn. 11 It is interesting that the σ DOS is suppressed more by scattering, because it becomes zero only 0.7 eV above E F . Thus the σ bands and their strong coupling with B vibrations, which are responsible for the high T c of MgB 2 , have an intrinsic weakness due to the proximity of the top edge of the band to the Fermi level.…”
Section: Basic Properties Of Mgbmentioning
confidence: 99%
“…In addition, pinning is increased by including a fi ne dispersion of defects, whose separation should match the vortex spacing and whose size should be comparable with the coherence length. 11 The best results are obtained by adding carbon in elemental form (microspheres, nanotubes, nanodiamond) or by C-containing compounds such as SiC, TiC, B 4 C, and organic compounds. Also nitrides, borides, and silicides as well as several metal oxides have been added, often yielding encouraging results.…”
Section: Superconducting Properties Of Mgbmentioning
confidence: 99%